Subspecies of Pleurota bicostella (Clerck, 1759) revisited and descriptions of nine new species in the P. bicostella species group (Lepidoptera: Gelechioidea: Oecophoridae: Pleurotinae) - Tabell, Jukka; Wikström, Bo; Mutanen, Marko; Bruckner, Harald; Sihvonen, Pasi (Zootaxa, 2021)
The identities of five subspecies of Pleurota bicostella (Clerck, 1759) are studied, and each is raised from subspecies to species: P. andalusica Back, 1973, stat. nov.; P. aragonella Chrétien, 1925, stat. rev.; P. asiatica Back, 1973, stat. nov.; P. illucidella Chrétien, 1915, stat. rev.; P. lepigrei Lucas, 1937, stat. rev. Nine new Pleurota species which all belong to the P. bicostella species group are described: P. agadirensis Tabell, sp. nov.; P. aprilella Tabell, sp. n.; P. karsholti Tabell, sp. nov.; P. kullbergi Tabell, sp. nov.; P. monochroma Tabell, sp. nov.; P. murina Tabell, sp. nov.; P. paragallicella Tabell, sp. nov; P. phaeolepida Tabell, sp. nov., all from Morocco; and P. dalilae Tabell, sp. nov. from Tunisia. Adult males and females, and their genitalia are illustrated. DNA barcodes of the aforementioned species are compared with those of all other Pleurotinae available to us in the BOLD database. Each of the presented and barcoded species has a unique BIN (Barcode Index Number).